Kesejahteraan Sekolah dan Kenakalan Remaja Siswa Sekolah Menengah Kejuruan - Sthepvanny Herlof A.I. Laure; Yeni Damayanti; Juliana Marlyn Y. Benu; Luh Putu Ruliati (Journal of Health and Behavioral Science, 2020)
School is essential during the process of students individual growing. School well-being important to be paid attention to in order to provide comfort for students. A research proves that one student will be comfortable getting surrounded by friendly teachers and friends who bring positive influence at school. Students of school with unfriendly environment behave negatively by doing things like playing truant, fighting with other students, smoking, and vandalism which are known as student’s delinquencies. This research aims to observe the relationship of school well-being with juvenile delinquencies by students in SMKN 2 Kota Kupang. This is a quantitative research used 330 students. The result proves that there is a significant negative relationship between the two variables which is -0.255 with the significance value of 0.000. The result also shows that there is a significant negative relationship among all of the aspects of school well-being with the delinquency.